2008
DOI: 10.2109/jcersj2.116.1283
|View full text |Cite
|
Sign up to set email alerts
|

Particle size dependence of CO2 absorption rate of powdered Li4SiO4 with different particle size

Abstract: Particle size dependence of CO2 absorption rate of powdered Li4SiO4 with four kinds of particle sizes was studied by SEM observation, particle size distribution measurement, and thermogravimetry. Average particle sizes of the powdered single phase Li4SiO4 samples were estimated about 26 μm, 34 μm, 53 μm, 70 μm, respectively by the particle size distribution measurement and SEM observation. The measurement of apparent rate constant k for the CO2 absorption reaction showed that k values of all the powdered Li4Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…6) Furthermore, LiFeO2 has an advantage over other lithium salts such as Li2ZrO3, 7) Li4SiO4, 4), 8) and Li4TiO4 9) because it absorbs CO2 and releases CO2 at lower temperatures than other compounds. 6) However, the CO2 absorption ratio of LiFeO2 is low because the formation of Li2CO3 on the surface of LiFeO2 particles 6) prevents CO2 molecules from diffusing inside the particles.…”
Section: ) -5)mentioning
confidence: 99%
“…6) Furthermore, LiFeO2 has an advantage over other lithium salts such as Li2ZrO3, 7) Li4SiO4, 4), 8) and Li4TiO4 9) because it absorbs CO2 and releases CO2 at lower temperatures than other compounds. 6) However, the CO2 absorption ratio of LiFeO2 is low because the formation of Li2CO3 on the surface of LiFeO2 particles 6) prevents CO2 molecules from diffusing inside the particles.…”
Section: ) -5)mentioning
confidence: 99%
“…Lithium-containing oxides, such as Li 2 ZrO 3 and Li 4 SiO 4 , have been investigated as CO 2 absorbents [1][2][3][4] and, in particular, Li 4 SiO 4 has much attention because of its high CO 2 absorption efficiency, which is supposed to depend on the following reaction (1). 4 Li 4 SiO 4 ðsÞ þ CO 2 ðgÞ $ Li 2 CO 3 ðsÞ þ Li 2 SiO 3 ðsÞ ð 1Þ…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the mass variation for CO 2 absorption saturated at 12.7% after 15 h and that the mass variation for CO 2 desorption saturated at À11.4% after 16 h. Therefore, it can be concluded that Ba 2 (Fe 1Àx In x ) 2 O 5 reversibly reacts with CO 2 by reaction (3). It was observed that the mass variation for CO 2 absorption saturated at 12.7% after 15 h and that the mass variation for CO 2 desorption saturated at À11.4% after 16 h. Therefore, it can be concluded that Ba 2 (Fe 1Àx In x ) 2 O 5 reversibly reacts with CO 2 by reaction (3).…”
Section: October 2014mentioning
confidence: 90%